Anti-Corruption Education Values in Lampung People's Life Philosophy - Muhammad Candra Syahputra; Andrian Anwar L. Nata (JUSPI (Jurnal Sejarah Peradaban Islam), 2021)
Anti-corruption values have existed in the local wisdom of the culture of each region in the country, in this case the author examines the values of anti-corruption education in the philosophy of life of Lampung people. This research is a literature study (library research) using a qualitative approach, while the sources in this research are books, journals, proceedings, and scientific manuscripts related to the topic of discussion. The results of this study show that anti-corruption values namely honesty, discipline, responsibility, hard work, modest, independent, fair, brave, caring are found in the philosophy of life of the Lampung people or the philosophy of piil pesenggiri which is also in harmony with Islamic values.